NEW DIMENSIONS OF FARMING: COMPROMISE AGRICULTURE: खेती के नये आयामः समझौता कृषि - Kesharwani, Harish (International Journal of Research -GRANTHAALAYAH, 2015)
The major issue is the improvement and development of agriculture as a result of increasing population, changing lifestyles, commercialization of agricultural products as well as seasonal variability, changes in production trend and agricultural inequality. Regardless of the extent of human development, but its supply will be either from the ground or its processing. Changes in the agricultural system can also be seen as a result of all kinds of changes in the context of agriculture. Also, the world's population is increasing rapidly and in the context of India, it is a fact that it is the second most populous country in the world, by 2030 it will overtake China to become the world's most populous country. Also, the population of India increases by 2 crore people every year, for which the demand for bread, cloth, house demand also increases. बढ़ती जनसंख्या, बदलती जीवन शैली, कृषिगत उत्पादों का व्यवासायीकरण के साथ साथ मौसमी परिवर्तनशीलता, उत्पादन प्रवृत्ति मे बदलाव और कृषिगत विषमता के परिणाम स्वरूप सबसे प्रमुख मुददा कृषि के सुधार और विकास का है। मानव अपने विकास की चाहे जो सीमा निर्धारित कर ले परंतु उसकी उदरपूर्ति जमीन से उगे आनाज या उसके प्रसंस्करण से ही होगी। कृषि के संदर्भ मे तमाम प्रकार के बदलावों के परिणाम स्वरूप कृषि प्रणाली मे भी बदलाव देखे जा सकते हैं। साथ ही विश्व की जनसंख्या तेजी के साथ बढ़ रही है तथा भारत के संदर्भ मे यह तथ्य है कि यह विश्व की दूसरी सर्वाधिक जनंख्या वाला देश है जो 2030 तक यह चीन को पीछे छोड़ते हुए विश्व की सर्वाधिक आबादी वाला देश हो जाएगा। साथ ही भारत की आबादी मे प्रतिवर्ष 2 करोड़ लोग बढ़ जाते है जिनकी आवश्यकता हेतु रोटी, कपड़ा, मकान की माॅग मे भी वृद्धि होती जाती है।